Synthesizing Multiple Stakeholder Perspectives on Using Virtual Reality to Improve the Periprocedural Experience in Children and Adolescents: Survey Study - Ahmadpour, Naseem; Weatherall, Andrew David; Menezes, Minal; Yoo, Soojeong; Hong, Hanyang; Wong, Gail (JMIR Publications, 2020)
BackgroundVirtual reality (VR) technology is a powerful tool for augmenting patient experience in pediatric settings. Incorporating the needs and values of stakeholders in the design of VR apps in health care can contribute to better outcomes and meaningful experiences for patients. ObjectiveWe used a multiperspective approach to investigate how VR apps can be designed to improve the periprocedural experiences of children and adolescents, particularly those with severe anxiety. MethodsThis study included a focus group (n=4) and a survey (n=56) of clinicians. Semistructured interviews were conducted with children and adolescents in an immunization clinic (n=3) and perioperative setting (n=65) and with parents and carers in an immunization clinic (n=3) and perioperative setting (n=35). ResultsQualitative data were examined to determine the experience and psychological needs and intervention and design strategies that may contribute to better experiences for children in three age groups (4-7, 8-11, and 12-17 years). Quantitative data were used to identify areas of priority for future VR interventions. ConclusionsWe propose a set of ten design considerations for the creation of future VR experiences for pediatric patients. Enhancing patient experience may be achieved by combining multiple VR solutions through a holistic approach considering the roles of clinicians and carers and the temporality of the patient's experience. These situations require personalized solutions to fulfill the needs of pediatric patients before and during the medical procedure. In particular, communication should be placed at the center of preprocedure solutions, while emotional goals can be embedded into a procedure-focused VR app to help patients shift their focus in a meaningful way to build skills to manage their anxiety.